KEPADATAN BAKTERI COLIFORM PADA TANAMAN AIR DI UPTD LABORATORIUM LINGKUNGAN DINAS LINGKUNGAN HIDUP BANYUWANGI - Novitasari, Amanda (Program Studi Biologi, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas PGRI Banyuwangi, Jalan Ikan Tongkol No 01, Telp (0333) 421593, 428592 Banyuwangi 68416, 2025)
This study aims to determine the density of coliform bacteria on aquatic plants at the Environmental Laboratory of the Banyuwangi Environmental Agency using the Most Probable Number (MPN) method. The sampled aquatic plants include Hydrilla verticilata (algae), Pistia stratiotes (water lettuce), and Cyperus papyrus (papyrus). The results indicate that the highest coliform bacteria density was found on Pistia stratiotes with a value of 200 MPN/g, while the lowest was on Cyperus papyrus with less than 180 MPN/g. Environmental factors such as temperature, humidity, and lighting influence the presence and distribution of coliform bacteria around these aquatic plants. This research provides valuable insights into water quality management and the sustainability of aquatic plants within the ecosystem.